Energy system for nearly zero energy family buildings: Experience from operation - Tomas Matuska; Borivoj Sourek; Michal Broum (Energy Reports, 2020)
Advanced concept of energy system for space heating, hot water preparation in new family buildings has been developed. Energy system consists of innovative heat pump (5.5 kW) extracting the heat from two environments: ground and ambient air. Heat pump is coupled with simple seasonal ground storage of heat built under the house and with photovoltaic system (6 kW) installed on the roof. In case of excess photovoltaic (PV) electricity in summer, the heat pump with variable speed compressor adapts its electric power to PV system power, extracts the heat from ambient air and transfers the heat into seasonal ground storage without external electric energy input. The ground storage is charged to 30 °C in upper level during the summer. In winter, heat pump uses the heat from ground storage and transfers it through the heat pump cycle for space heating with high effectivity. The experimental system has been installed in newly built house in Hamry (CZ) and it is operated for two seasons so far. Results from the monitoring show radical reduction of electricity use from external grid. System uses more than 80 % of energy from renewables. Specific non-renewable primary energy use for space heating, hot water preparation and auxiliary energy is about 15 kWh/m2 per year.
Keywords: 330; Heat pump; Seasonal storage; Nearly zero energy building; NZEB